Postural habits and postural awareness in spinal pain, spinal function, and quality of life in resident physicians - Elzem Bolkan Günaydın (Gülhane Tıp Dergisi)
Aims: Evaluation of postural habits and awareness scale (PHAS), Spinal Functional Index (SFI), and Nottingham Health Profile (NHP) scores, and spinal pain presence (location, intensity, and duration) in resident physicians. Methods: This cross-sectional study was conducted on resident physicians. Whether participants experienced spinal pain, location (neck, back, low-back), as well as the duration, were recorded. They were asked to mark pain intensity at rest and during movement, in spinal pain areas on a 0-10 cm visual analog scale (VAS). Afterwards, the PHAS, SFI, and NHP questionnaires were applied. Results: A total of 72 resident physicians were included (mean age: 27.81±3.98 years); 41 (56.9%) were female. In the neck pain group, the PHAS-stance habits and awareness (SHA) score was moderately negatively correlated with neck pain duration (r=-0.44, p=0.006) and low to moderately positively correlated with the SFI score (r=0.33, p=0.05). The PHAS-ergonomic awareness (EA) score showed a moderate negative correlation with neck pain intensity-movement VAS (r=-0.39, p=0.02). In the back pain group, PHAS-SHA (r=0.52, p=0.004) and PHAS-postural habit (PH) scores (r=0.37, p=0.05) were positively correlated with SFI score at moderate and low moderate levels. In the low-back pain group, PHAS-PH (r=-0.47, p=0.006) and PHAS-EA (r=-0.45, p=0.01) were negatively and moderately correlated to VAS for pain intensity during movement. PHAS-positional awareness score correlated moderately positively with SFI score (r=0.41, p=0.02). PHAS-SHA correlated moderately negatively with pain intensity-movement VAS (r=-0.40, p=0.02), and low to moderately positively with SFI (r=0.37, p=0.04). Conclusions: Poor PH and awareness are associated with more severe and prolonged spinal pain, worse spinal function, and poorer quality of life.